-6(4-t)=12t

Apply the distributive property.

-6⋅4-6(-t)=12t

Multiply.

Multiply -6 by 4.

-24-6(-t)=12t

Multiply -1 by -6.

-24+6t=12t

-24+6t=12t

-24+6t=12t

Subtract 12t from both sides of the equation.

-24+6t-12t=0

Subtract 12t from 6t.

-24-6t=0

-24-6t=0

Add 24 to both sides of the equation.

-6t=24

Divide each term in -6t=24 by -6.

-6t-6=24-6

Cancel the common factor of -6.

Cancel the common factor.

-6t-6=24-6

Divide t by 1.

t=24-6

t=24-6

Divide 24 by -6.

t=-4

t=-4

Solve for t -6(4-t)=12t